2007
DOI: 10.1213/01.ane.0000260265.53212.fe
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Oxygen Desaturation After Cardiopulmonary Bypass in a Patient with Raynaud's Phenomenon Detected by Near-Infrared Cerebral Oximetry

Abstract: Raynaud's phenomenon is characterized by episodes of arterial vasospasm precipitated by cold stress, usually affecting the digits of the hands. There is controversy about the occurrence of vasospasm in internal organ systems. In this report, we present a case of Raynaud's peripheral vasospasm accompanied by cerebral oxygen desaturation as detected by near infrared cerebral oximetry after separation from cardiopulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In a patient with Raynaud's phenomenon, a bilateral drop in rSO 2 with concomitant loss of finger pulse oximetry was reversed with intravenous nitroglycerin after separation from CPB. 20 Likewise, other authors have shown that optimization of rSO 2 may help prevent hypoxic brain injury and reduce length of hospital stay in higher risk patients undergoing major abdominal surgery. 21 Reduction in rSO 2 also predicts postoperative cognitive dysfunction in thoracic surgery 22 and is a reliable indicator of clamping ischemia in carotid endarterectomy.…”
Section: Discussionmentioning
confidence: 98%
“…In a patient with Raynaud's phenomenon, a bilateral drop in rSO 2 with concomitant loss of finger pulse oximetry was reversed with intravenous nitroglycerin after separation from CPB. 20 Likewise, other authors have shown that optimization of rSO 2 may help prevent hypoxic brain injury and reduce length of hospital stay in higher risk patients undergoing major abdominal surgery. 21 Reduction in rSO 2 also predicts postoperative cognitive dysfunction in thoracic surgery 22 and is a reliable indicator of clamping ischemia in carotid endarterectomy.…”
Section: Discussionmentioning
confidence: 98%
“…Our group has recently shown in our porcine model that controlled periods of hypoxia to a SpO 2 target of 70% lead to a TSI% decrease of 10.5 ± 1% as recorded by the PortaMon NIRS sensor from the animal's hindlimb 49 . While clinically, such www.nature.com/scientificreports/ severe episodes of hypoxia are unlikely to be encountered on a routine basis; other investigators have reported decreases in NIRS-derived tissue saturation indices in various clinical settings that lead to tissue hypoperfusion, including vascular disease 50 and shock [51][52][53] .…”
Section: Discussionmentioning
confidence: 99%
“…22 Evidence of cerebral, not just skin, hypoperfusion associated with RD includes de novo recurrent infarctions in a patient with RD and migraine with aura 12 and of cerebral oxygen desaturation after cardiopulmonary bypass in a patient with RD. 23 Single-photon emission computed tomographic analysis showed deterioration in preexisting cerebral perfusion defects in patients with secondary RP subjected to a cold stress test. 24 Vasoconstriction in human microcirculation in subarachnoid hemorrhage 22 and focal arteriolar vasospasm in the retina of a patient with migraine 25 have been documented.…”
Section: Brainstem Ischemia Cerebral Vasospasm and Rpmentioning
confidence: 99%